Facteurs environnementaux de proximité et choix résidentiels - Sandrine Gueymard (Développement Durable et Territoires)
According to opinions pools, environmental quality appears nowadays as a deciding factor in residential choices wheareas it has been marginalized for a long time. In this background of households growing sensitivity for life quality and changes in public action in particular concerning environment, the precise measurement of environmental amenities is now a crucial issue for local decidors, specially in urban areas. The purpose of this paper is to feed reflection about valorisation of environmental factors of proximity by an analyse of residential preferences, uses, perceptions and representations developped by houselhold to them contact. We will develop this subject, basing ourselves on a exploratory research work focused on a particular environmental factor, which is characteristic of urban areas: green spaces.